Desenvolvimento de um aplicativo para a criacão de um diário de lugares utilizando GPS e imagens da câmera de dispositivos móveis com android - Meurer, Fernando (2012)
The interaction between people happens since the dawn of the human race. This interacion arose from the need of communication from man to play sounds in order to represent their natural world and facilitate interaction with other individuals. With the passage of time and the evolution of humans with the environment that surrounds them, tools and methods of communication were being created and refined. Existing technologies currently provide the ability to communicate in many different ways, making any distance almost irrelevant, for example television, radio, telephone and most of all communication tools today, the Internet. In order to raise the level of interaction and communication, this work proposes the development of a mobile application, this based on the Android operating system, which manages a travel diary, wherein the user can mark the places they have visited and index photos, which can then be stored on a server on the Internet and shared with others. To achieve this goal, the resource was used Global Positioning System (GPS) and the camera of the mobile devices, working together in a web application which will serve only as consultation of data, but with the possibility of sharing large network. To share data on a server, a web application was developed using the GWT framework. As a result, we developed a simple and intuitive program, basic requirements for mobile applications.